Manajemen strategis pada bank syariah: Tinjauan literatur tentang upaya peningkatan kinerja - Haq, Arti Mar’atul (Maliki Interdisciplinary Journal, 2025)
Sharia banking in Indonesia has great potential for growth, but still faces challenges such as a limited market size, low financial literacy, and the need for innovation. In this situation, strategic management is very important because it can link the organization’s vision with appropriate operational actions. This article reviews the literature related to the application of strategic management in Islamic banks and its relationship with performance. The results of the literature review show that the application of strategic management through SWOT analysis, service digitization, and risk management can improve efficiency, competitiveness, and customer satisfaction in Islamic banks. However, most previous studies still discuss these aspects separately. This article contributes by presenting a comprehensive review of the integration of these various strategies, which can serve as a basis for further research and strategic management practices in Islamic banking.